Investigation of 1.5 kW secondary side power controlled method in a inductive wireless power transfer system - Bhavsingh, Bhukya; Gotluru, Suresh Babu; Bhukya, Mangu; Bhukya, Ravikumar (Institute of Advanced Engineering and Science, 2024)
The contemporary and utilitarianism of the existing consumer world is advancing towards the better world technical benefits in the electrical world such as wired phase to wireless phase utilizing its volatile features. This paper addresses the battery performance in constant current (CC), constant voltage (CV) through inductive wireless power transfer (IWPT) systems. To analyze this workable mode, the researcher has proposed the series-series (S-S) compensation topology which is load independent current output. While charging the battery through wireless, the coil resistance is found to be affected by the battery's current and power. To figure out a practical solution, the researcher has introduced novel closed loop bi-directional switches with duty cycle control. The existing theoretical and simulated results have been analyzed with 1.5 kW, 120 mm air-gap and 85 kHz frequency. In this connection, the researcher has self-developed a prototype to better understand the theoretical perceptions of the proposed WPT system.